Importance of the system of social protection for transformation in Bosnia and Herzegovina: Our plan for Bosnia - Хелмут Браун, PhD; Никола Шпирић, PhD (Acta Economica, 2006)
After a terrible civil war, Bosnia and Hercegovina (BiH) has been reconstructed politically in 1995. The complexity of the political structure, however, makes BiH fragile due to different conflicting interests of the respective ethnicities. This ethnical nationalism and a weak administration of BiH as a whole make economic transition more difficult. Compared to other central-east and south-east states transformation could start in BiH only later and with support respectively under pressure from outside. To alleviate the problems accompanying the difficult transformation which should stabilise the fragile construction of the state. In this article we present a draft outlining the core elements of a modern system of social security for BiH as a plan for the political stabilization of the country.